Effects of pair bonding on dopamine D1 receptors in monogamous male titi monkeys (Callicebus cupreus). Issue 3 (18th October 2016) - Hostetler, Caroline M.; Hinde, Katherine; Maninger, Nicole; Mendoza, Sally P.; Mason, William A.; Rowland, Douglas J.; Wang, Guobao B.; Kukis, David; Cherry, Simon R.; Bales, Karen L.
Abstract : Pair bonding leads to increases in dopamine D1 receptor (D1R) binding in the nucleus accumbens of monogamous prairie voles. In the current study, we hypothesized that there is similar up‐regulation of D1R in a monogamous primate, the titi monkey ( Callicebus cupreus ). Receptor binding of the D1R antagonist [ 11 C]‐SCH23390 was measured in male titi monkeys using PET scans before and after pairing with a female. We found that within‐subject analyses of pairing show significant increases in D1R binding in the lateral septum, but not the nucleus accumbens, caudate, putamen, or ventral pallidum. The lateral septum is involved in a number of processes that may contribute to social behavior, including motivation, affect, reward, and reinforcement. This region also plays a role in pair bonding and paternal behavior in voles. Our observations of changes in D1R in the lateral septum, but not the nucleus accumbens, suggest that there may be broadly similar dopaminergic mechanisms underlying pair bonding across mammalian species, but that the specific changes to neural circuitry differ. This study is the first research to demonstrate neuroplasticity of the dopamine system following pair bonding in a non‐human primate; however, substantial variability in the response to pairing suggests the utility of further research on the topic.